2022
DOI: 10.3389/fimmu.2022.1070961
|View full text |Cite
|
Sign up to set email alerts
|

PD-1/PD-L1 checkpoint inhibitors in advanced hepatocellular carcinoma immunotherapy

Abstract: Hepatocellular carcinoma (HCC) has a high prevalence and mortality rate worldwide. Sorafenib monotherapy has been the standard of first-line treatment for advanced HCC for a long time, but there are still many shortcomings. In recent years, with the deepening of research on tumor immune microenvironment, researchers have begun to explore new approaches in immunotherapy, and the introduction of immune checkpoint inhibitors has brought fundamental changes to the treatment of HCC. Programmed cell death protein 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 163 publications
1
39
0
Order By: Relevance
“…High PD‐L1 expression can impair effector T cell performance and hasten their depletion, preventing them from efficiently identifying and killing cancer cells. [ 57 ] The high expression of PD‐L1 in liver cancer also offers a chance for immunotherapy, specifically immune checkpoint blocking therapy, making this type of cancer prone to ICIs, specifically aPD‐1 or aPD‐L1 antibodies. Immunotherapies that target the PD‐1/PD‐L1 pathway can interfere with the PD‐1/PD‐L1 interaction and restore the antitumor immune response.…”
Section: Resultsmentioning
confidence: 99%
“…High PD‐L1 expression can impair effector T cell performance and hasten their depletion, preventing them from efficiently identifying and killing cancer cells. [ 57 ] The high expression of PD‐L1 in liver cancer also offers a chance for immunotherapy, specifically immune checkpoint blocking therapy, making this type of cancer prone to ICIs, specifically aPD‐1 or aPD‐L1 antibodies. Immunotherapies that target the PD‐1/PD‐L1 pathway can interfere with the PD‐1/PD‐L1 interaction and restore the antitumor immune response.…”
Section: Resultsmentioning
confidence: 99%
“…This combination therapy regimen was well tolerated, and the toxicity was easily controlled [ 32 ]. Recently, a Himalaya phase III study demonstrated that both durvalumab combined with tremelimumab (anti-CTLA-4) and durvalumab monotherapy significantly improved the survival of HCC patients [ 33 ]. However, several challenges have yet to be addressed, such as the low remission rate and the lack of applicable standards.…”
Section: Discussionmentioning
confidence: 99%
“…After the up-regulation of PD-1, HBV-speci c CD8 + T lymphocytes are in a highly depleted and hypofunctional state. Therefore, PD-1/PD-L1 immune checkpoint inhibitors (ICIs) become a new approach to treat hepatocellular carcinoma [32,33]. As we all know, immune escape exerts a critical effect on HNC occurrence and development, thus immunotherapy is a good choice.…”
Section: Discussionmentioning
confidence: 99%